Discourse Analysis of Conflict and Resolution in History Textbooks: Representations of the Referendum in Indonesia - Arif Saefudin; Susilo Setyo Utomo; Malkisedek Taneo; I Made Ratih Rosanawati; Loso Judijanto; Ulyan Nasri; Muhammad Zulkifli Amin; Sudarto; Siti Andini (Forum for Linguistic Studies, 2024)
This study explores how Indonesian history textbooks represent conflict and its resolution with a focus on the theme of East Timor. The research applies the methodology of Historical Discourse Analysis, examining various elements of representation, including nomination, predication, argumentation, perspective, and intensification. The primary objects of study are two Indonesian history textbooks that are currently used in schools. The results show that textbook I adopts a pragmatic and binary approach, framing the Indonesian government as the protagonist that seeks to include East Timor as part of its national territory. In this narrative, the East Timorese people are portrayed as the antagonists who resist the integration process with Indonesia. This approach reflects a polarized view of the conflict, emphasizing the roles of both parties in opposition. On the other hand, Textbook II takes a more constructive and reconciliation-oriented approach. It presents a vision for future cooperation and understanding between Indonesia and East Timor, highlighting possibilities for peaceful resolution and long-term collaboration between the two countries. Despite these different approaches, this study identifies an ongoing challenge in the writing of Indonesian history textbooks, which can be termed as "schizo-history." This concept refers to the paradox faced by historians in balancing efforts to reconstruct historical events with the anxiety surrounding the potential impact of those narratives on national unity. The study argues that Indonesian historians must continue to seek alternative methodologies that can address these tensions while providing more nuanced and balanced representations of historical events. This research contributes to broader discussions on the role of history textbooks in shaping national identity and calls for further investigation into the challenges and opportunities in writing history textbooks in post-conflict contexts.